2009
DOI: 10.3166/rfg.191.93-108
|View full text |Cite
|
Sign up to set email alerts
|

Le risque opérationnel bancaire. Dispositif d'évaluation et système de pilotage

Abstract: Distribution électronique Cairn.info pour Lavoisier. © Lavoisier. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…These research results confirm first and foremost the hypothesis according to which an expert activity such as trading is likely to engender immeasurable operational risks (Meric & Sfez, ). Meric and Sfez, like Lamarque and Maurer () before them, suggest that, beyond flat metrics and mapping, controlling these risks is a management problem. If we grant that the object of such research could be to produce engineering‐level knowledge (Martinet & Pesqueux, ), the reflexive expression of trading practices could provide the basis for the development of new control mechanisms.…”
Section: Discussion: Trading Expertise—a Manageable Operational Risk?mentioning
confidence: 95%
See 1 more Smart Citation
“…These research results confirm first and foremost the hypothesis according to which an expert activity such as trading is likely to engender immeasurable operational risks (Meric & Sfez, ). Meric and Sfez, like Lamarque and Maurer () before them, suggest that, beyond flat metrics and mapping, controlling these risks is a management problem. If we grant that the object of such research could be to produce engineering‐level knowledge (Martinet & Pesqueux, ), the reflexive expression of trading practices could provide the basis for the development of new control mechanisms.…”
Section: Discussion: Trading Expertise—a Manageable Operational Risk?mentioning
confidence: 95%
“…The nature of operational risk management (Lamarque & Maurer, 2009) suggests that a solution may be found in informal control-that is, in power relationships as opposed to authority (Bouquin, 2011). In their literature review on fraud, Le Maux, Smaïli, and Ben Amar (2013) also suggested that positive-accounting hypotheses did not provide adequate solutions, notably because traders currently enjoy a considerable margin of authority under their superiors.…”
Section: How To Control the Experts: Turning Expertise Against Itselfmentioning
confidence: 99%
“…Les résultats de cette recherche confirment en premier lieu l’hypothèse selon laquelle une activité d’expert telle que le trading est susceptible d’engendrer des risques opérationnels immesurables (Meric et Sfez, ). Ils suggèrent, à l’instar de Lamarque et Maurer (), qu’au‐delà d’une métrique et d’une cartographie à plat, la maîtrise de ces risques est un problème de management. Si l’on admet que l’objet d’une telle recherche puisse être celui de produire une connaissance d’ordre ingénierique (Martinet et Pesqueux, ), il faut parvenir à trouver dans l’expression réflexive de la pratique des traders un point d’appui pour concevoir des dispositifs de contrôle renouvelés.…”
Section: Discussion : L’expertise Du Trading Un Risque Opérationnel unclassified
“…Le renvoi à la gestion managériale des risques opérationnels (Lamarque et Maurer, ) incite à trouver une réponse au problème dans le contrôle informel, c’est‐à‐dire dans les relations de pouvoir et non d’autorité (Bouquin, ). A l’occasion d’une revue de littérature centrée sur la fraude, Le Maux, Smaïli et Ben Amar () suggèrent eux aussi que les hypothèses issues de la théorie positive de la comptabilité ne fournissent pas de réponses suffisantes au problème.…”
Section: Discussion : L’expertise Du Trading Un Risque Opérationnel unclassified
“…Those internal models aim to assess and to measure the risk exposure at a consolidated level (the "group" level), and are supposed to allow the requirement in regulatory capital to be reduced. If we consider the credit risk management (with the implementation of the IRB 11 approach and the need to calculate the credit loss parameters, or with the use of a Var-credit measure) or the operational risk management (Lamarque & Maurer, 2009), it is obvious that an appropriate process requires the building of large databases. Of course, this standardized approach can not be led by each of the local/regional co-operative banks.…”
Section: The Compliance With the Pruden-tial Requirements: An Opportumentioning
confidence: 99%